Computerized wheeze detection in young infants: comparison of signals from tracheal and chest wall sensors. (21st November 2016) - Puder, Lia C; Wilitzki, Silke; Bührer, Christoph; Fischer, Hendrik S; Schmalisch, Gerd
Abstract: Computerized wheeze detection is an established method for objective assessment of respiratory sounds. In infants, this method has been used to detect subclinical airway obstruction and to monitor treatment effects. The optimal location for the acoustic sensors, however, is unknown. The aim of this study was to evaluate the quality of respiratory sound recordings in young infants, and to determine whether the position of the sensor affected computerized wheeze detection. Respiratory sounds were recorded over the left lateral chest wall and the trachea in 112 sleeping infants (median postmenstrual age: 49 weeks) on 129 test occasions using an automatic wheeze detection device (PulmoTrack ® ). Each recording lasted 10 min and the recordings were stored. A trained clinician retrospectively evaluated the recordings to determine sound quality and disturbances. The wheeze rates of all undisturbed tracheal and chest wall signals were compared using Bland–Altman plots. Comparison of wheeze rates measured over the trachea and the chest wall indicated strong correlation ( r ⩾ 0.93, p < 0.001), with a bias of 1% or less and limits of agreement of within 3% for the inspiratory wheeze rate and within 6% for the expiratory wheeze rate. However, sounds from the chest wall were more often affected by disturbances than sounds from the trachea (23% versus 6%, p < 0.001). The study suggests that in young infants, a better quality of lung sound recordings can be obtained with the tracheal sensor.